The instrumental value of advance directives: lesson learned from the COVID-19 pandemic for policymaking - Elisabeth Stock; Christian H. Nickel; Bernice S. Elger; Andrea Martani (Research in Health Services & Regions)
Abstract Open conversations between patients and healthcare professionals (HCP) are required to evaluate which treatments are reasonable for the individual case, especially towards the end of life. Advance Care Planning (ACP), which often results in drafting an Advance Directive (AD), is a useful tool to help with decisions in these circumstances, but the rate of AD completion remains low. During the COVID-19 pandemic, ACP and AD gained popularity due to the alleged advantage that they could facilitate resource allocation, to the benefit of public health. In this article, which presents a theoretical reflection grounded in scientific evidence, we underline an even stronger ethical argument to support the implementation of AD in end-of-life care (eol-C) i.e. the instrumental value at the individual level. We show, with particular reference to lessons learned from the COVID-19 pandemic, that AD are instrumentally valuable in that they: (1) allow to thematise death; (2) ensure that overtreatment is avoided; (3) enable to better respect the wish of people to die at their preferred place; (4) help revive the “lost skill” of prognostication. We thus conclude that these arguments speak for promoting the territorially uniform implementation and accessibility of high-quality AD in care.